What about the roundabout ? : The European Senneberg Competition. - Brenninkmeijer, Carl; Deleu, Luc; Pil, Lut (Vilvoorde : Stichting Senneberg, 1999)
Aballi, Ignasi ; Airo, Mario ; Cabrita Reis, Pedro ; Cattelan, Maurizio ; Cazal, Philippe ; Chafes, Rui ; Colomer, Jordi ; De Cordova, Denise ; Cox, Paul ; Delvoye, Wim ; Fillitz, Stephan ; Fleury, Sylvie ; Kasimir, Marin ; Klopf, Karl Heinz ; Kulnari, Nayan ; Leccia, Ange ; van Lieshout, Joep ; Ostrowski, Aribert von ; Signer, Roman ; Weiss, Albert
Engels
What about the roundabout ?, Stadshal Vilvoorde, 1999-05-29 - 1999-06-07. It ran from 1 April to 26 May in the European headquarters of C&A
kunstcatalogus
Keywords: Klopf, Karl Heinz